Mental Health Burden After Injury: It's About More than Just Posttraumatic Stress Disorder. Issue 6 (December 2021) - Herrera-Escobar, Juan P.; Seshadri, Anupamaa J.; Stanek, Ewelina; Lu, Kaye; Han, Kelsey; Sanchez, Sabrina; Kaafarani, Haytham M. A.; Salim, Ali; Levy-Carrick, Nomi C.; Nehra, Deepika
Abstract : Objective: Assess the prevalence of anxiety, depression, and posttraumatic stress disorder (PTSD) after injury and their association with long-term functional outcomes. Background: Mental health disorders (MHD) after injury have been associated with worse long-term outcomes. However, prior studies almost exclusively focused on PTSD. Methods: Trauma patients with an injury severity score ≥9 treated at 3 Level-I trauma centers were contacted 6–12 months post-injury to screen for anxiety (generalized anxiety disorder-7), depression (patient health questionnaire-8), PTSD (8Q-PCL-5), pain, and functional outcomes (trauma quality of life instrument, and short-form health survey)). Associations between mental and physical outcomes were established using adjusted multivariable logistic regression models. Results: Of the 531 patients followed, 108 (20%) screened positive for any MHD: of those who screened positive for PTSD (7.9%, N = 42), all had co-morbid depression and/or anxiety. In contrast, 66 patients (12.4%) screened negative for PTSD but positive for depression and/or anxiety. Compared to patients with no MHD, patients who screened positive for PTSD were more likely to have chronic pain odds ratio (OR): 8.79 [95% confidence interval (CI): 3.21, 24.08], functional limitations [OR: 7.99 (95% CI: 3.50, 18.25)] and reduced physical health [ β : −9.3 (95% CI: −13.2, −5.3)]. Similarly, patients who screened positive for depression/anxiety (without PTSD) were more likely to have chronic pain [OR: 5.06 (95% CI: 2.49, 10.46)], functional limitations [OR: 2.20 (95% CI: 1.12, 4.32)] and reduced physical health [ β : −5.1 (95% CI: −8.2, −2.0)] compared to those with no MHD. Conclusions: The mental health burden after injury is significant and not limited to PTSD. Distinguishing among MHD and identifying symptom-clusters that overlap among these diagnoses, may help stratify risk of poor outcomes, and provide opportunities for more focused screening and treatment interventions.